2019
DOI: 10.3390/molecules24061131
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits the Migration and Metastasis of MDA-MB-231 Human Breast Cancer by Reversing TGF-β1-Induced Epithelial-Mesenchymal Transition

Abstract: Metastasis is a major cause of death in patients with breast cancer. In the process of cancer development, epithelial-mesenchymal transition (EMT) is crucial to promoting the invasion and migration of tumor cells. In a previous study, the role of resveratrol in migration and metastasis was investigated in MDA-MB-231 (MDA231) human breast cancer cells and a xenograft-bearing mouse model. Additionally, the related mechanism was explored. In the present study, in vitro Transwell assays showed that resveratrol can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 42 publications
3
83
0
2
Order By: Relevance
“…By acting as a cytotoxic agent, RE can halt the progression and metastasis of cancer cells through the inhibition of angiogenesis and invasion of primary tumor cells. Hence, RE can be used to prevent cancer formation at its early stages or halt the progression and subsequent metastasis by acting as a cytotoxic agent [202][203][204][205][206].…”
Section: Resveratrol Impacts Cancer Onset: Clinical Studiesmentioning
confidence: 99%
“…By acting as a cytotoxic agent, RE can halt the progression and metastasis of cancer cells through the inhibition of angiogenesis and invasion of primary tumor cells. Hence, RE can be used to prevent cancer formation at its early stages or halt the progression and subsequent metastasis by acting as a cytotoxic agent [202][203][204][205][206].…”
Section: Resveratrol Impacts Cancer Onset: Clinical Studiesmentioning
confidence: 99%
“…RV is a nutraceutical polyphenol with anti-cancer potential. 22 , 37 , 38 RV has been shown effective in causing cancer cell death and cancer cell senescence 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 and to inhibit cancer cell invasion and metastasis 30 , 47 , 48 , 49 in several in vitro and in vivo models, including ovarian cancer. 30 , 42 , 49 It has been shown that autophagy contributes to RV-induced apoptosis in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, TGF-β can stimulate EMT via Smad2 and Smad3 activation, leading to an increase in N-cadherin and vimentin levels, and a decrease in E-cadherin levels. The administration of Res suppresses the metastasis of breast cancer (under both in vitro and in vivo conditions) via the inhibition of TGF-β1 and down-regulation of Smad2 and Smad3 [ 177 ]. TGF-β also contributes to the migration and malignant behavior of lung cancer.…”
Section: Resveratrol and Tgf-β Signaling Pathwaymentioning
confidence: 99%